OPTIMASI PRODUKSI WIRE HARNESS DI PT SURYA TEKNOLOGI BATAM - Akhmad Ihksanudin; Paskaria Loyda Tarigan, Elsya (Computer Science and Industrial Engineering, 2024)
Production optimization is an effort to improve the production process by reducing or eliminating production processes that do not provide added value or commonly referred to as waste. Wire harness is one of the electronics production produced by PT Surya Teknologi Batam. Based on 7 months data in July 2023 - February 2024, it was found that the production output was not achieved. For example in July where the production target is 5000pcs while the actual production obtained is 3,485pcs. This study aims to determine the causes of unachieved production output and find out how to achieve production output. The analysis method used is Lean Manufacturing with Value Stream Mapping method, to analyze the cause of waste, fishbone diagram is used. This research identified four wastes, motion has the highest weight of 25.9%, over processing has a weight of 25.6%, waiting 24.3%, and followed by defects which have the lowest weight of 24.2%. Several ways can be done to achieve production output, including improvements to waste in motion, over processing, waiting, and defects. Motion by applying the 5S concept and providing special storage racks for form by off (equipment). Over processing by implementing a monitoring system that can provide warnings to employees if there is a shortage of materials. Waiting by increasing the number of operators in the machine process to speed up the processing procedure. Defect by providing training on the importance of being thorough and setting a schedule for routine preventive maintenance for label printers. Based on future state mapping, the process cycle efficiency value is 92.56% which was previously 72.23% which means an increase of 28.1%, this indicates an increase in productivity in the wire harness production process.